Answer:
x = -
Step-by-step explanation:
To find f(g(x)) substitute x = g(x) into f(x), that is
f(g(x))
= f(x + 1)
= 2(x + 1)² ← expand using FOIL
= 2(x² + 2x + 1) ← distribute
= 2x² + 4x + 2
To find g(f(x)) substitute x = f(x) into g(x), that is
g(f(x))
= g(2x²)
= 2x² + 1
----------------------------------------------------------
Equating gives
2x² + 4x + 2 = 2x² + 1 ( subtract 2x² + 1 from both sides )
4x + 1 = 0 ( subtract 1 from both sides )
4x = - 1 ( divide both sides by 4 )
x = -
Answer:
B
Step-by-step explanation:
The first term has a power and the second term doesnt have a power.
Hope it helped. Pls mark me as brainliest.
Answer:
...
Step-by-step explanation:
..
Answer:
The next two terms are 92 and 105.
Step-by-step explanation:
79 + 13 = 92
92 + 13 = 105
Answer:
x° = 40°
Step-by-step explanation:
142° = 3x° + 22° (Vertically opposite angles)
3x° = 120°
x° = 40°